Problem of hepatocellular carcinoma in West Africa - Ladep, Nimzing G (World J Hepatol, 2014)
The incidence of hepatocellular carcinoma (HCC) is known to be high in West Africa with an approximate yearly mortality rate of 200000. Several factors are responsible for this. Early acquisition of risk factors; with vertical or horizontal transmission of hepatitis B (HBV), environmental food contaminants (aflatoxins), poor management of predisposing risk factors and poorly-managed strategies for health delivery. There has been a low uptake of childhood immunisation for hepatitis B in many West African countries. Owing to late presentations, most sufferers of HCC die within weeks of their diagnosis. Highlighted reasons for the specific disease pattern of HCC in West Africa include: (1) high rate of risk factors; (2) failure to identify at risk populations; (3) lack of effective treatment; and (4) scarce resources for timely diagnosis. This is contrasted to the developed world, which generally has sufficient resources to detect cases early for curative treatment. Provision of palliative care for HCC patients is limited by availability and affordability of potent analgesics. Regional efforts, as well as collaborative networking activities hold promise that could change the epidemiology of HCC in West Africa.